Some Issues of Prevention of Youth Crime in the Republic of Armenia - Simonyan, T. (Bulletin of Yerevan University C: Jurisprudence, 2020)
It is known that crime prevention is a system of state and public measures aimed at neutralization or reducing the impact of factors, which are the causes and conditions of crime. It is impossible to totally prevent crimes, as it is impossible to completely neutralize all its causes and conditions. The maximum that is possible to do, is to conduct an economic, institutional, ideological, cultural, psychological measures aimed at overcoming the negative effects in these areas. This will limit the growth of crime or, at best, reduce its level1 . V.V. Luneev rightly notes that only strengthening legal and criminological control over criminal behavior can reduce the level of crime in particular society, and here priority should be given to criminological control, since it is the most effective and radical2 . Strong impact on the causes and conditions of crime, both by its results and by its volume, is the main direction in the prevention of crime3 . The socialization of a young person is largely influenced by the varieties of factors which are concerned to economic situation, peculiarities of the family of the young person, the education, working environment, relations with peers, etc. In fact, it can be stated that a person does not exist outside of society and social relations, and his activities, the choice of one or another mode of behavior (including criminal) in different life situations is ultimately associated with these relationships. Moral norms and rules are not genetically inherited by man, they are not the fruits of evolution. These norms are passed on as social experience from generation to generation through education4 . The formation of a personality at the initial stages is closely related to imitation of behavior, when a person adopts the forms of behavior adopted in his immediate environment. These forms of behavior can determine both the further normal development of the personality and its degradation and socially dangerous activity. Socialization in the family can play a decisive role in shaping the identity of the offender, and the negative impact of the family can become an 1 Vetrov, N.I .. Prevention of Offences among the Youth. Moscow, 1980, p. 69. 2 Luneev, V.V. Crime of the XX Century. Moscow, 1997, p. 475. 3 Alekseev, A.I. , Gerasimov S.I. , Sukharev A.Y. ... Criminological Prevention: Theory, Experience, Problems. M., 2001, p. 4. 4 Dubinin. Social and Biological in the Contemporary Problem of Man. Problems of Philosophy, 1972, no. 10, p. 51. 17 insurmountable obstacle to the normal development of the personality. This is the reason that in the prevention of youth crime, first of all, it is necessary to pay attention to the neutralization of criminogenic factors in the family of a young person.
Keywords: crime, prevention, family, groups, personality, alienation and maladjustment, neutralization, reducing, factors, immediate measures, preliminary and direct prevention, influences